THE MEDIATED PARTNERSHIP MODEL ON MICRO WASTE SCALE BUSINESS - Anik Martinah Hariati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
Post-eruption in 2010, agricultural land in the mountain Bromo covered with volcanic ash. breaktrough is needed to overcome this problem because agriculture is still the backbone of most of the population's inhabitants, Farming without land becomes a strategic solution and common mushroom (Agracius bisporus) becomes an option, considering the potential of this business is still open. The demand for common mushrooms increased with a positive growth trend in line with the growing hospitality and culinary industry in East Java. But unfortunately the common mushroom has not been much developed in Indonesia. This is an opportunity for innovative market players to monopolize agribusiness-based common mushroom. The farmer groups in Sukapura Probolinggo sub-district have tried to cultivate common mushroom through partnership pattern. IbW-CSR program that became the basis of writing this article, from the beginning is designed as a collection point to follow up the cooperation team of devotees with PKBL PT. Bank Mandiri Malang. Through this program, it is expected that vertical integration from upstream to downstream of common mushroom-based agribusiness clusters can be built so that gradually farmer groups can build product competitiveness and strengthen focal position in mushroom commodity market.